Próba klasyfikacji typologicznej glinianych przęślików tarnobrzeskiej kultury łużyckiej - Jabłkowska, Aleksandra (Muzeum Okręgowe w Rzeszowie, 2021)
The aim of the article is to present an attempt at typological classification of clay spindle whorls of the Tarnobrzeg Lusatian culture. It is a closely related category with textiles, but still quite often marginalized by archaeologists in the studies of the excavation materials. It is probably the effect of their commonness and obvious purpose. In opposition to such perception of this category of sources, a much broader aspect of the role of spindle whorls in phenomena of sociocultural and economic importance will be presented. Spindle whorls can be a starting point for research on the recognition and reconstruction of the weaving of the population of the Tarnobrzeg Lusatian culture, research on the chronology and cultural relations of the described taxonomic unit as well as research on its rituals and social structures.

The article deals with the issues of clay spindle whorls of the Tarnobrzeg Lusatian culture. It is a category of artefacts closely related to the textile manufacturing, but still quite often marginalized by archaeologists in the studies of the excavation materials. It is probably the effect of their commonness and obvious purpose. They are usually mentioned in short in the form of descriptions and figures. The article presents the first attempt at typological classification of clay spindle whorls of the Tarnobrzeg Lusatian culture, which was developed on the basis of the variability of the shapes of cross-sections of spindle whorls. In that way it was possible to distinguish eight basic types – spindle whorls with a rectangular crosssection (type I), spindle whorls with a lenticular cross-section (type II), spindle whorls with a biconvex cross-section (type III), spindle whorls with a plano-convex cross-section (type IV), spindle whorls with a convexo-concave cross-section (type V), spindle whorls with a lenticular-rectangular crosssection (type VI), spool-shaped spindle whorls (type VII) and miniature vessel shaped spindle whorls (type VIII). The material scope of the present research includes the finds of 129 spindle whorls coming from 41 sites of the Tarnobrzeg Lusatian culture. The analysed category of artefacts includes items discovered both at settlement and sepulchral sites, however, it should be noted that the items recorded in the second context are much rarer. The conclusions drawn from the research presented in the article are the issue of standardizing and systematizing the descriptions of spindle whorls in archaeological publications. In general, the descriptions should take into account the following data: the shape of the cross-section, the diameter, the height measured at the opening, the weight and any features visible on the external surfaces of the spindle whorls in the form of ornaments or damage. The secondary features are colour and an admixture tempering the clay. All the abovementioned parameters allow us to obtain a relatively complete image of an individual item and therefore they are helpful for archaeologists whose field of interest is prehistoric textiles. Moreover, remarkably valuable information is also the listing of this category of artefacts together with the materials found in a given feature, which allows drawing conclusions regarding their chronology. In addition, the article discusses the issues in the broadest possible range, aimed at presenting and developing various aspects related to spindle whorls. Due to detailed analyses, it has been proved that the spindle whorls can be a starting point for research on the importance of spindle whorls as a source for analysing and reconstructing the weaving of the population of the Tarnobrzeg Lusatian culture, research on the chronology and cultural relations of the described taxonomic unit as well as research on its rituals and social structures.
An attempt at typological classification of clay spindle whorls of the Tarnobrzeg Lusatian culture
Niniejsze opracowanie jest nieznacznie zmienioną wersją pracy licencjackiej napisanej pod kierunkiem prof. dr. hab. Sylwestra Czopka i obronionej na Wydziale Socjologiczno-Historycznym Uniwersytetu Rzeszowskiego w 2017 roku.
Keywords: spindle whorls; Tarnobrzeg Lusatian culture; Bronze Age; Early Iron Age; south-eastern Poland